Application and progress of 3D printed biomaterials in osteoporosis - Wang, Chenxu; Liu, Aiguo; Zhao, Ziwen; Ying, Ting; Deng, Shuang; Jian, Zhen; Zhang, Xu; Yi, Chengqing; Li, Dejian (Frontiers in Bioengineering and Biotechnology, 2025)
Osteoporosis results from a disruption in skeletal homeostasis caused by an imbalance between bone resorption and bone formation. Conventional treatments, such as pharmaceutical drugs and hormone replacement therapy, often yield suboptimal results and are frequently associated with side effects. Recently, biomaterial-based approaches have gained attention as promising alternatives for managing osteoporosis. This review summarizes the current advancements in 3D-printed biomaterials designed for osteoporosis treatment. The benefits of biomaterial-based approaches compared to traditional systemic drug therapies are discussed. These 3D-printed materials can be broadly categorized based on their functionalities, including promoting osteogenesis, reducing inflammation, exhibiting antioxidant properties, and inhibiting osteoclast activity. 3D printing has the advantages of speed, precision, personalization, etc. It is able to satisfy the requirements of irregular geometry, differentiated composition, and multilayered structure of articular osteochondral scaffolds with boundary layer structure. The limitations of existing biomaterials are critically analyzed and future directions for biomaterial-based therapies are considered.